GE_GERICHTE P/9394/2015 vom 13. September 2016 - GE Cour de justice (2016)
APPRÉCIATION DES PREUVES; COMMERCE DE STUPÉFIANTS; COAUTEUR(DROIT PÉNAL); FIXATION DE LA PEINE; HÉROÏNE | CPP10; LStup19.1.b; LStup19.1.d; LStup19.2.a; CP47